PENYALAHGUNAAN NARKOTIKA OLEH PEGAWAI NEGERI SIPIL DILIHAT DARI PERSPEKTIF KAJIAN KRIMINOLOGI (STUDI KASUS POLRES GORONTALO KOTA) - Firanti Oktaviani Igirisa; Darmawati, Darmawati; A. Siti Kumala Ilyas (Unisan Law Review, 2024)
The aim of this research is (1) To determine and analyze the factors that cause narcotics abuse by civil servants in Gorontalo City. (2) As well as efforts to overcome narcotics abuse by civil servants in Gorontalo City. The type of research used by researchers in compiling this research is empirical research. The approaches used by researchers in compiling this research include: Legislative Case approach. The results of the research show (1) that the factors causing narcotics abuse involving civil servants in Gorontalo City are caused by several factors, both internal and external factors, internal factors namely trying to abuse narcotics, and external factors namely trying to abuse narcotics. environmental factors of residence and social environment. (2) And efforts to overcome narcotics abuse by Civil Servants are carried out starting from preventive efforts carried out through counseling and outreach about the dangers of narcotics, repressive efforts in the form of law enforcement actions carried out by the Gorontalo Regional Police and Class IIA Prisons in Gorontalo City, and carrying out rehabilitation efforts social and physical, apart from carrying out regular urine tests in every agency, there must be regular outreach and strict legal action against civil servants who abuse narcotics. The results of this research recommend (1) that punishment in Indonesia be increased in implementing sanctions against criminals, especially narcotics perpetrators. (2) Existing facilities and infrastructure in correctional institutions are improved and professional staff are added to correctional institutions so that their guarding can be more effective.